Hypermedia-Based E-Book - Basuki wibawa; Bintang Petrus Sitepu; Awaludin Awaludin (International Journal of Multi Discipline Science, 2018)
E-book is a digital form of printed book which includes digital information in the form of text, image, audio and video. Hypermedia-based e-book is a digital book with text, image, audio, video and animation where these multimedia components are connected.   Thus it enables someone to access information provided from different places quickly. In order to develop hypermedia-based E-book, some learning theories can be taken into consideration such as behaviorist theory, cognitive theory, constructivist theory and system learning approach.  The advantages of hypermedia-based e-book are (1) enabling students to work on assignment individually or in group, (2) monitoring learning progress, (3) attractive size and composition, (4) the content can be customized to suit the learner’s context, (5) learners can be active in constructing the content, (6) mental involvement and higher-order thinking process development, (7)the content of E-book is relevant with the learner’s prior knowledge, (8) the content enables the learners to work together to comprehend the information, (9) teachers can be supervisors, (10) the questions are challenging and realistic for learners, (11) learners can interact with E-book. Besides, E-book also possesses some disadvantages such as (1) special skills to make and design hypermedia-based E-book, (2) special tools needed to access E-book, (3) for inexperienced user, accessing E-book can be quite difficult.